Impact of short-term exposure to fine particulate matter air pollution on urinary metabolome: A randomized, double-blind, crossover trial. (September 2019) - Chen, Chen; Li, Huichu; Niu, Yue; Liu, Cong; Lin, Zhijing; Cai, Jing; Li, Weihua; Ge, Wenzhen; Chen, Renjie; Kan, Haidong
Abstract: Background: Metabolomics is a novel tool to explore the biological mechanisms of the health effects of fine particulate matter (PM2.5 ) air pollution. Very few studies have examined the urinary metabolomic changes associated with PM2.5 exposure. Objective: To assess the alternation in urine metabolomics in response to short-term PM2.5 exposure. Methods: We conducted a randomized, double-blind, crossover trial of 9-day real or sham indoor air purification among 45 healthy college students in Shanghai, China. Urine samples were collected immediately at the end of each intervention stage and were analyzed for metabolomics using ultrahigh performance liquid chromatography-mass spectrometry. Orthogonal partial least square-discriminant analysis and linear mixed effect models were used to examine metabolomic changes between interventional scenarios and their associations with continuous PM2.5 exposure. Results: The time-weighted average personal PM2.5 exposure in the real-purified scenario was 50% lower than in the sham-purified air scenario (28.3 μg/m 3 VS 56.9 μg/m 3 ). A total of 40 differentiated urinary metabolites at a false discovery rate <0.05 were identified for the effects of both intervention and continuous PM2.5 exposure, including 16 lipids, 5 purine metabolites, 2 neurotransmitters, and 3 coenzymes. Conclusions: This real-world randomized crossover trial demonstrated that short-term PM2.5 exposure could result in significant changes in urinary metabolomic profile, which may further lead to perturbation in energy metabolism, oxidative stress and inflammation. Highlights: Limited evidence on exploration of PM2.5 effects with urine metabolomics approach We designed a randomized, double-blind, crossover trial of air purifiers. We identified 16 lipids, 5 purines, 2 neurotransmitters, and 3 coenzymes. PM2.5 results in energy metabolism perturbation, oxidative stress and inflammation.